Implementasi Fuzzy Logic untuk Menentukan Kelayakan Pembangunan Infrastruktur: Implementasi Fuzzy Logic untuk Menentukan Kelayakan Pembangunan Infrastruktur - Barus, Ertina Sabarita; Zendrato, Niskarto (LPPM UNIKA Santo Thomas, 2021)
A computer simulation application system that can analyze the benefits of developing an infrastructure development project in a sub-district and simulated in the fuzzy toolbox application Matlab 7.9.2 In analyzing the benefits of infrastructure development, several economic rules and feasibility studies for infrastructure development are used, namely aspects of benefits, aspects of effectiveness and aspects of efficiency . These rules are applied to the results of the benefit data when infrastructure development is carried out in the first year, then the results of the benefit data are processed using Mamdani fuzzy logic reasoning which consists of 2 inference processes. In processing fuzzy input data, it produces output from the inference process which is then classified into 5 eligibility conditions, namely, low, normal, high, very high and not feasible, which are used as a means of supporting infrastructure development decisions in an area